Using three-dimensional kinematics to identify feedback for the snatch: A case study - Lester, H.; Kuok, W.; Williams, M. D.; Wilson, C. J.; Meehan, D. L. (The Journal of Strength and Conditioning Research, 2011)
This case study evaluated the importance of peak bar velocity and starting posture adopted by a novice weightlifter to the outcome of a Snatch lift. Multiple observations of both successful and unsuccessful attempts were captured using 3D motion analysis (VICON MX: 500 Hz). The following data analysis was then used to derive feedback. In total, 133 attempts of loads ranging from 75 to 100% of 1 repetition maximum (1RM) were performed by the subject (age = 25 years, stature = 171 cm, mass = 74.8 kg, Snatch 1RM = 80 kg). Variables included peak bar velocity, pelvis, hip, knee and ankle joint angles at the starting position for the right side and the difference between (left minus right) sides. No main effects for load, success, or their interactions were found for peak bar velocity. Starting position kinematics were mostly nonsignificant between the outcome of Snatch attempts. Right ankle joint angle was the only exception, where unsuccessful attempts displayed greater (p = 0.0228) dorsiflexion. A more comprehensive finding was achieved through the partition modeling; this analysis provided valuable insight and coaching feedback for the subject in relation to his lower body kinematics at the starting position. Furthermore, the accuracy of this feedback was verified using a holdback data set. Specifically, anterior pelvic tilt (>17.6°) and hip joint (<89.6°) angle were identified as the key features to increasing the likelihood of success. In conclusion, this case study outlines a method of data collection and analysis to assist coaching feedback for an individual.